PENGENALAN APLIKASI PEMBELAJARAN TANDA LALU LINTAS MENGGUNAKAN SINGLE MARKER PADA PENDIDIKAN ANAK USIA DINI BERBASIS ANDROID - Pertiwi, Dara Sapta; Suryadi, Ahmad (Jurnal Manajamen Informatika Jayakarta, 2024)
Education about traffic signs is an important aspect in forming children's safety awareness from an early age. However, this learning is often met with challenges in maintaining the interest and involvement of young children. To overcome this, the development of an Android-based learning application with single marker augmented reality (AR) technology has been carried out. This application aims to provide interactive and fun traffic sign learning for young children. Using AR technology, children can interact directly with traffic signs in a realistic virtual environment. Interactive features, such as sound explanations and rewards, coupled with child-friendly display designs, are expected to increase children's interest in learning and understanding of traffic signs. Through this application, it is hoped that children can gain solid knowledge about traffic signs while remaining engaged and motivated in the learning process. Thus, this application can potentially be an effective tool in supporting efforts to create a generation that is more aware and safe in traffic in the future.